Penerapan Model Pembelajaran Teams Games Tournament (TGT) untuk Meningkatkan Hasil Belajar Siswa Melalui Media Kokami - Siti Khotimatus Suhro; Haning Hasbiyati; Laila Khusnah (FKIP Universitas Islam Jember, 2017)
This study aims to improve student learning outcomes on the subject of human motion system by applying learning Teams Games Tournament (TGT) using the Kokami media. Researchers conducted observations in class VIII MTs Nurul Yaqin Sukorambi and approximately 45% of the data obtained show student score ≥ 70 in precycle. The study was conducted in two cycles, each cycle consisting of four phase: planning, action, observation and research reflection. This type of research is the Classroom Action Research (CAR). Based on the results obtained, the percentage of student learning outcomes by 75% the first cycle and the second cycle by 85%. The results of the daily test scores of students in the first cycle values ​​obtained 78,85 and 86,65 second cycle values ​​obtained. It proves that the Application of Learning Teams Games Tournament using Kokami can improve student learning outcomes. Keywords: Teams Games Tournament (TGT), Kokami, Learning Outcomes.